Mitral valve blood cyst with atrial septal aneurysm treated as rheumatic valvular heart disease: a case report and review of literature - Kedir Negesso Tukeni; Kidus Tesfaye Bezabih; Tamirat Godebo Woyimo; Elsah Tegene Asefa (Journal of Medical Case Reports)
Abstract Background Mitral blood cyst with atrial septal aneurysm is a unique instance of rare occurrence in medical literature. It is crucial for the discipline of cardiology to address the special difficulties that come with diagnosing and treating these two diseases together. The goal of this case report is to provide a comprehensive overview of the clinical presentation, diagnostic challenges, and treatment strategies for this uncommon cardiac disease in a resource-limited setting. Case presentation This is a case involving a 50-year-old Ethiopian female patient referred to our hospital for cardiac evaluation. She presented with intermittent palpitation to a nearby health center, which was diagnosed as rheumatic heart disease, for which she was on intramuscular benzathine penicillin injection on a monthly basis. Otherwise, she had no history suggestive of acute rheumatic fever and no chest pain, body swelling, orthopnea, or paroxysmal nocturnal dyspnea, historically or on current presentation. Evaluations revealed that her chest was clear and resonant with good air entry, and flat jugular venous pressure, but she had a grade III pansystolic murmur best heard at the apex that radiates to the left axilla. No other pertinent physical examination findings were discovered. Echocardiographic evaluation revealed a tiny cyst at the apex of posterior mitral valve leaflet with interatrial septal bulging into the right atrium. Conclusion Cardiac blood cysts are an uncommon congenital cardiac condition that can lead to stroke and other potentially fatal consequences, especially if they are situated on the mitral valve. With improved specialists and low-risk procedures, surgical removal is advised. Given the patient’s state, a proper diagnosis was therefore essential to provide her with accessible management options in this setting while she waits for a definitive surgical treatment in case the need arises.